The Phonographic Author of Milton, Edison and Uzanne - Larisa Kocic-Zámbó (Presses Universitaires de la Méditerranée, 2021)
This paper maps the connection of Milton and Edison in the late Victorian imagination as examples of geniuses. I argue that their juxtaposition is rooted in the voice hearing etymology of the genius, but more importantly in the notion of what I call the phonographic author. Drawing on nineteenth-century periodicals and books, I will be comparing Edison’s own vision of the phonograph in authoring books and the Victorian popular imagination elaboration on the same, especially in Uzanne’s short story ‘The End of Books’ (1894) while showing Milton’s own role in making such an idea of the phonographic author feasible.